New Species of Begonia section Baryandra (Begoniaceae) from Northwestern Luzon, Philippines - Calaramo, Michael Agbayani; Rubite, Rosario Rivera; Pugal, Cora Marie; Lin, Chei-Wei (Phytotaxa, 2019)
Another Begonia is discovered from the northwestern tip of the Island of Luzon, Philippines. Begonia palemlemensis is a vigorous Begonia growing in the tropical montane rainforest of Kalbario Patapat Natural Park in the municipalities of Adams and Pagudpud, Ilocos Norte. The species resembles Begonia droseroides in having a hirsute indumentum. It is named after the mountain where it was first documented, Mt. Palemlem. The new rare Begonia species was discovered during the Biophysical Assessment Monitoring survey commissioned by the Department of Environmental and Natural Resources Region I in 2018. No populations on adjacent mountains were recorded.